From Brussels to Bogor: Contacts, Networks and the History of the Bandung Conference 1955 - Wildan Sena Utama (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2016)
This article discusses the roots of the Bandung Conference of 1955 by tracing the alliance of Asian and African worldwide internationalism and anti-imperialism that existed since the early twentieth century. It attempts to show that although the conference emerged during the height of the Cold War, the network behind this alliance had gradually developed since the interwar period. The solidarity of this alliance lay in the common history of the colonized people that struggled to become sovereign. Contacts, meetings and conferences that took place in Europe and Asia juxtaposed the anti-imperialist movement of Asian and African countries. This article argues that the Bandung Conference 1955 was the culmination of relationships and connections of an Afro-Asian group who had been long oppressed by colonialism, racism and class superiority.